Interleukin-6 promoter haplotypes are associated with etanercept response in patients with rheumatoid arthritis. Issue 12 (December 2015) - Schotte, Heiko; Schmidt, Hartmut; Gaubitz, Markus; Drynda, Susanne; Kekow, Jörn; Willeke, Peter; Schlüter, Bernhard
Abstract Indices prognosticating anti-tumor necrosis factor (TNF) response in patients with rheumatoid arthritis are a matter of interest. Differential outcome under anti-TNF and anti-interleukin-6 (IL-6) therapy raises the question whether genetic polymorphisms that have previously been linked to IL-6 production are associated with response to anti-TNF therapy. Fifty (50) rheumatoid arthritis (RA) patients were treated with etanercept (median 36 weeks, range 4–52). In terms of the EULAR response criteria, 25 patients responded well, 17 patients moderately and 8 patients not. By direct sequencing, the patients and 91 matched healthy controls were genotyped for the IL-6 promoter SNPs -597G > A (rs1800797), -572G > C (rs1800796) and -174G > C (rs1800795) and for an AnTn microsatellite tract at -373. Alleles and haplotypes were tested for association with disease susceptibility and therapy response. No significant difference was seen in the genotype distribution between patients and healthy controls. Confirming the results of previous studies, we observed a trend of -174G being more frequent in patients with a good or moderate therapy response. Beyond that, carriage of the A9T11 microsatellite allele within the -174G haplotype was associated most closely with a favourable response (relative risk 1.31; 95 % confidence interval 1.02–1.68). A subtle analysis of the IL-6 promoter giving respect to its complex haplotypic structure results in more precise information as to the association of genotypes with the long-term etanercept response. Despite a conclusive hypothesis that a genetically determined IL-6-dominated RA responds less well to anti-TNF, more work has to be done to provide us with reliable information regarding the functional aspects of these genetic polymorphisms.